Estudo, análise e simulação computacional de acoplamentos indutivos wireless utilizando software de elementos finitos - Macedo, Tatiana Saviato (2019)
The research in inductive power transfer rising fastest in recent years. It was explained mainly because of the convenience and safety that this technology offers for a wide range of applications. This work presents a parameter analysis of coil systems used for inductive power transfer such as the geometry of coils, size of the coils, a distance of transmission, coupling coefficient, level of power and efficiency. To find the parameters the finite element software was available. Both geometries, circular coil, and square coil were studied to evaluate the magnetic field behavior for many distances of transmission and conditions of misalignments. The work also analyzed theoretically influence the use of electromagnetic shielding on the performance for inductive transfer systems. To add shielding in coils systems improves coupling factor up to 62%, and its effect is greater on square coils. However, the coupling factor is higher for circular coils even when adding a shield at the coils. To validate the theoretical results was compared simulation model data with experimentals data from a prototype. Comparative analysis has shown that the use of finite element tools is valid for parameter calculation and magnetic field behavior analysis, even in conditions os spatial misalignment between inductive power transfer system coils. Both theoretical and experimental results have shown that to ensure higher levels of load transfer power, the size of the coils was between 2 and 3.3 times the distance os transmission. In this distance, the magnetic flux between the coils reaches its maximum point. We concluded that static inductive transfer systems, circular coils perform better than square coils when the distance os transmissions are less than half their size.